2016
DOI: 10.1088/1367-2630/18/2/023006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing lattice structures in phase space

Abstract: In one dimensional systems, it is possible to create periodic structures in phase space through driving, which is called phase space crystals (Guo et al 2013 Phys. Rev. Lett. 111 205303). This is possible even if for particles trapped in a potential without periodicity. In this paper we discuss ultracold atoms in a driven optical lattice, which is a realization of such a phase space crystals. The corresponding lattice structure in phase space is complex and contains rich physics. A phase space lattice differs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 56 publications
(92 reference statements)
1
47
0
Order By: Relevance
“…The effective interaction coefficients U ij depend on the atomic s-wave scattering length g 0 , shapes of | ( )| w x t , i 2 and how densities of different Wannier wavepackets overlap in the course of time evolution on the classical resonant orbit. Despite the fact that the original interactions between ultra-cold atoms are contact, the effective interactions can be long-range [35,42,93]. Moreover, they can be controlled by changing the s-wave scattering length in space and periodically in time by means of a Feshbach resonance, i.e.…”
Section: A Time Crystal Haldane Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The effective interaction coefficients U ij depend on the atomic s-wave scattering length g 0 , shapes of | ( )| w x t , i 2 and how densities of different Wannier wavepackets overlap in the course of time evolution on the classical resonant orbit. Despite the fact that the original interactions between ultra-cold atoms are contact, the effective interactions can be long-range [35,42,93]. Moreover, they can be controlled by changing the s-wave scattering length in space and periodically in time by means of a Feshbach resonance, i.e.…”
Section: A Time Crystal Haldane Phasementioning
confidence: 99%
“…This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34]. However, periodically driven systems can also reveal a whole variety of condensed matter phases in the time domain even if no spontaneous process is involved in the emergence of such crystalline structures in time [28,[35][36][37][38][39][40] (see [41][42][43][44] for phase space crystals). Indeed, if a single-or many-body system is driven resonantly, its resonant dynamics can be reduced to solid state-like behavior and importantly such condensed matter physics emerges not in the configuration space but in the time domain-e.g.…”
Section: Introductionmentioning
confidence: 99%
“…where k B is the Boltzmann constant and T eff is the effective temperature in the rotating frame. In [55], we have investigated a similar driven system and showed that the effective temperature T eff equals to the real temperature if the local ground states near the stable points of phase space lattice are the standard coherent states. Actually, the positive and negative sublattices shown in figure 2(a) make no difference in the frame of Floquet theory.…”
Section: T H X P T H X P H X P T H X P T H X P H X Pmentioning
confidence: 99%
“…Here, T is the chosen stroboscopic time step and T is the time-ordering operator. Exotic Floquet Hamiltonians [43][44][45][46][47][48][49] which are inaccessible in static systems can be engineered from equation (1.1) and a range of novel physical phenomena, such as Floquet topological physics [50][51][52][53], phase space crystals [54,55], Anderson localization in time domain [56][57][58] and spontaneous breaking of discrete time-translation symmetry (Floquet time crystals) [59][60][61][62][63][64][65][66][67], can be created by Floquet engineering [68][69][70]. While most work focus on the singleparticle physics of (dissipative) Floquet systems, the possible new physics by Floquet many-body engineering has become an active research direction in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation